Antibacterial Effectiveness Test of Wrap Leaf Extract (Smilax rotundifolia) Against Escherichia coli and Propionibacterium acnes Bacteria - Heti Aisyah; Irwandi Irwandi; Angga Bayu Budiyanto; A.M. Muslihin (Postgraduate, University of Mataram, 2025)
Diarrhea and acne, caused by the bacteria Escherichia coli and Propionibacterium acnes, are common illnesses in children and adults. Antibiotics can overcome bacterial infections, but cases of antibiotic resistance are increasing. This study aims to determine the effect of wrap leaf extract (Smilax rotundifolia) on the growth of P. acnes and E. coli. This research can support microbiology-based science learning that utilizes biodiversity for students. Phytochemical tests showed that the extract contained flavonoids, alkaloids and saponins. The results of antibacterial testing showed that wrap leaf extract was able to inhibit the growth of P. acnes bacteria from concentrations of 10% and 15% with an average inhibition of 5.31 mm and 6.42 mm, and the positive control (Amoxicillin) had an inhibition of 7.26 mm. However, E. coli did not show any inhibition zone. The Mann-Whitney test results showed that the wrapper leaf extract has antibacterial effectiveness by comparing the negative control with a concentration of 10% and 15% and the positive control with a concentration of 10%. There is a difference between the concentration comparison where the Sig.<0.05 value. Then, comparing the positive control with a concentration of 15% produces a Sig.>0.05 value, meaning there is no difference between the two.